2017
DOI: 10.1080/02699052.2016.1229032
|View full text |Cite
|
Sign up to set email alerts
|

Role of resilience in the rehabilitation of adults with acquired brain injury

Abstract: While rehabilitation typically focuses on the identification and reduction of impairments for improving functioning, a focus on resilience may allow for recovery in a broader sense that exceeds expected outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…The association between psychosocial robustness and fatigue supports earlier findings linking resilience with less fatigue after TBI [ 77 ]. Trait extraversion, conscientiousness and optimism seemed to align with resilience factors in this protective dimension, while trait neuroticism, loneliness, behavioral inhibition and psychological distress were placed on the opposite side of this dimension, confirming that absence of negative emotionality is a prominent feature of psychosocial robustness.…”
Section: Discussionsupporting
confidence: 88%
“…The association between psychosocial robustness and fatigue supports earlier findings linking resilience with less fatigue after TBI [ 77 ]. Trait extraversion, conscientiousness and optimism seemed to align with resilience factors in this protective dimension, while trait neuroticism, loneliness, behavioral inhibition and psychological distress were placed on the opposite side of this dimension, confirming that absence of negative emotionality is a prominent feature of psychosocial robustness.…”
Section: Discussionsupporting
confidence: 88%
“…People with TBI have lower levels of resilience compared with the general population (Kreutzer et al 2016, Lukow et al 2015. Where risk factors increase a person's vulnerability to negative events, resilience factors such as self-determination, self-efficacy, and dynamism can increase a person with TBI's ability to adapt and thrive after their injury (Dumont et al 2004, Neils-Strunjas et al 2017, Lukow et al 2015. All but one of the adults with TBI had returned to using their usual social media platforms post-injury, and most had also taken up use of newer platforms.…”
Section: Discussionmentioning
confidence: 99%
“…There has been limited analysis of the psychometrics of this scale, however, in a sample of military service members with mild TBI, the internal consistency was high [Cronbach's α = 0.91; ( 76 )]. It has been suggested that the psychometric properties for the scale are likely to be strong due to the method of validation of the measure ( 77 ), which included focus groups, interviews, and patient consultation from individuals with TBI, clinicians, and caregivers of individuals with TBI. Additionally, item pools were tested in a large sample ( n = 675) and calibrated using item response theory methods.…”
Section: Methodsmentioning
confidence: 99%